Users and user study methodology: the JUBILEE project - Linda Banwell; Graham Coulson (Information Research: An International Electronic Journal)
This paper presents both theoretical aspects and practical examples from the on-going and large-scale JUBILEE (JISC User Behaviour in Information seeking: Longitudinal Evaluation of Electronic information services) project, now in its fifth year. Particular emphasis will be placed on the importance of using robust theory and methods as the basis for reputable user studies, especially those undertaken by practitioners. Theory underlying the development of the JUBILEE project and Toolkit is outlined, followed by demonstration of its practical use and impact during the project's on-going program of monitoring and evaluation activities. Themes underlying the paper concern the importance to practitioners of the need to understand and adopt a well founded methodology and sound methods with which to conduct projects, the additional benefits they can derive by so doing, and the pitfalls and dangers of not so doing. JUBILEE is used throughout as the example project to demonstrate the points made.